Globalization of Supply Chain Management and International Relations in World Economic - Z.K Radzhabova; O.R Radzhabov; M.M Osmanov; B.I Shikhsaidov; S.Z Hidirova; M.Yu Akhmedova (International Journal of Supply Chain Management, 2019)
At the present stage of the development of the world economy, suppl chain globalization is deepening the process of intertwining the national economies of the developed and developing world, reducing economic barriers to the cross-border movement of finances, goods, capital, and services, thereby facilitating their access to foreign markets. Under these conditions, the large-scale growth of incoming volumes of investment and financial resources that contribute to the creation of new jobs, the development of modern technologies, know-how, becomes the objective basis of structural transformations and increasing development rates. A whole series of trends cited in the article gives reason to believe that globalization is a more advanced stage of internationalization of all factors of production when the system of international economic relations unites all national economies, strengthening the integrity of the world. This is an objective process that concentrates the prerequisites and factors for the development of the modern world community, and above all the scientific, technical and economic progress.At the same time, the world community makes coordinated decisions in the system of international economic institutions, guided by agreed rules of conduct and unified procedures at the global level. All this turns the world economy into a holistic global organism, united by the international division of labor, and by the gigantic trade and economic structures, the global financial and information network, which is basically aimed at stable dynamics and growth.